The effect of different woods on the quality of smoked catfish (cryptoterus bicirchis) - Fara Adipa Sitompul; Mirna Ilza; Desmelati ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was intended to evaluate the effect of different woods on the quality ofsmoked catfish (Cryptoterus bicirchis). The fish weigthing ± 40 gram/fish was taken from thefisherman in Rokan Hilir. The fish was eviscerated and hot-smoked in smoke kiln with kandiswood (Garcinia xanthochymus), simpur wood (Dillenia sulfruticosa) and laban wood (Vitexpinnata). Smoked catfish was evaluated for sensory quality, phenol, acidity and pH. The resultshowed that the of smoked catfish smoked with kandis wood was the best in quality. Phenol,acidity and Ph value for the smoked catfish smoked with kandis wood was 6,30%, 3,51% and6,27 respectively; simpur wood was 3,68%, 2,19% and 6,40 respectively; and laban wood was3,99%, 2,36% and 6,48 respectivelyKeywords: smoked catfish, wood, hot smoking